2018
DOI: 10.1002/ecs2.2346
|View full text |Cite
|
Sign up to set email alerts
|

Landscape influence on the local distribution of western pond turtles

Abstract: Abstract. Spatial and temporal scales are important for understanding habitat associations because organisms have neither unbounded mobility nor perfect knowledge of their environment, but still must make decisions on where to seek food, shelter, and mates. Semi-aquatic turtles exemplify the need to evaluate potential habitat characteristics at a range of scales, because their ectothermy makes these animals particularly sensitive to local environmental conditions, yet their limited mobility spatially constrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…We scaled all climatological, environmental, and logging-associated covariates to have a mean of 0 and a standard deviation of 1 prior to modeling. We tested collinearity between covariates using Spearman's rank correlation in the package Hmsic version 4.2-0 (Harrell 2019) and removed all correlated covariates ( | r | > 0.7) from subsequent analysis. Additionally, as our data set consisted of 82 subplots (sampling units), with unique covariate values nested within 8 VES river reach sites, we included a random effect in all models to account for the nested spatial effect among subplots within the same VES river reach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We scaled all climatological, environmental, and logging-associated covariates to have a mean of 0 and a standard deviation of 1 prior to modeling. We tested collinearity between covariates using Spearman's rank correlation in the package Hmsic version 4.2-0 (Harrell 2019) and removed all correlated covariates ( | r | > 0.7) from subsequent analysis. Additionally, as our data set consisted of 82 subplots (sampling units), with unique covariate values nested within 8 VES river reach sites, we included a random effect in all models to account for the nested spatial effect among subplots within the same VES river reach.…”
Section: Discussionmentioning
confidence: 99%
“…Quantifying abundance and occupancy are an effective approach for determining the effects of disturbances, such as logging, on turtles (Horn and Gervais 2018, Čapkun‐Huot et al 2021). However, the detection of turtles is typically imperfect because of observer error (Nichols et al 2000), low population density, cryptic behaviors of individuals, or environmental conditions that influence the likelihood of detection (Gu and Swihart 2004).…”
mentioning
confidence: 99%
“…The presence of bullfrogs did not appear to impact WPT occupancy, a finding supported by Horn & Gervais (2018), who found no predictive relationship between bullfrog presence and pond occupancy by WPT in the North Umpqua watershed of Southwestern Oregon. Bullfrogs are capable of only consuming small sized turtles.…”
Section: Livestock Ponds and Habitat Featuresmentioning
confidence: 70%
“…However, the same study found that proximity to other wetlands was not a significant predictor for the Blanding's turtle (Emydoidea blandingii), due to it being a vagile species. Horn & Gervais (2018) found that WPT abundance in rivers increased as distance to nearest ponds and wetland habitat types increased, suggesting that WPTs are more likely to disperse to ponds when they are closer. Whether there is a significant difference between WPT occurrence in stock ponds and distance to the nearest WPT population is unknown.…”
Section: Livestock Ponds and Habitat Featuresmentioning
confidence: 96%
See 1 more Smart Citation